Phagocytosis by stroma confounds coculture studies - Herbst, Sophie; Stolarczyk, Marta; Becirovic, Tina; Czernilofsky, Felix; Liu, Yi; Kolb, Carolin; Knoll, Mareike; Herling, Marco; Müller-Tidow, Carsten; Dietrich, Sascha (iScience, 2021)
Signals provided by the microenvironment can modify and circumvent pathway activities that are therapeutically targeted by drugs. Bone marrow stromal cell coculture models are frequently used to study the influence of the bone marrow niche on ex vivo drug response. Here, we show that mesenchymal stromal cells from selected donors and NKTert, a stromal cell line, which is commonly used for coculture studies with primary leukemia cells, extensively phagocytose apoptotic cells. This could lead to misinterpretation of results, especially if viability readouts of the target cells (e.g. leukemic cells) in such coculture models are based on the relative proportions of dead and alive cells. Future coculture studies which aim to investigate the impact of bone marrow stromal cells on drug response should take into account that stromal cells have the capacity to phagocytose apoptotic cells.
Gesehen am 02.12.2021